Haemostatic support in postpartum haemorrhage: A review of the literature and expert opinion. Issue 1 (22nd January 2023) - Hofer, Stefan; Blaha, Jan; Collins, Peter W.; Ducloy-Bouthors, Anne-Sophie; Guasch, Emilia; Labate, Francesco; Lança, Filipa; Nyfløt, Lill Trine; Steiner, Kostja; Van de Velde, Marc
Abstract : Postpartum haemorrhage (PPH) remains the leading cause of pregnancy-related deaths worldwide. Typically, bleeding is controlled by timely obstetric measures in parallel with resuscitation and treatment of coagulopathy. Early recognition of abnormal coagulation is crucial and haemostatic support should be considered simultaneously with other strategies as coagulopathies contribute to the progression to massive haemorrhage. However, there is lack of agreement on important topics in the current guidelines for management of PPH. A clinical definition of PPH is paramount to understand the situation to which the treatment recommendations relate; however, reaching a consensus has previously proven difficult. Traditional definitions are based on volume of blood loss, which is difficult to monitor, can be misleading and leads to treatment delay. A multidisciplinary approach to define PPH considering vital signs, clinical symptoms, coagulation and haemodynamic changes is needed. Moreover, standardised algorithms or massive haemorrhage protocols should be developed to reduce the risk of morbidity and mortality and improve overall clinical outcomes in PPH. If available, point-of-care testing should be used to guide goal-directed haemostatic treatment. Tranexamic acid should be administered as soon as abnormal bleeding is recognised. Fibrinogen concentrate rather than fresh frozen plasma should be administered to restore haemostasis where there is elevated risk of fibrinogen deficiency (e.g., in catastrophic bleeding or in cases of abruption or amniotic fluid embolism) as it is a more concentrated source of fibrinogen. Lastly, organisational considerations are equally as important as clinical interventions in the management of PPH and have the potential to improve patient outcomes.